2013
DOI: 10.1111/pin.12087
|View full text |Cite
|
Sign up to set email alerts
|

A case of metastasizing pleomorphic adenoma in the maxillary bone appearing twenty years after initial resection of pleomorphic adenoma of the hard palate

Abstract: Metastasizing pleomorphic adenoma (MPA) is the inexplicable metastasis of a histologically benign pleomorphic adenoma (PA). Approximately 50 cases have been reported. A 62-year-old woman noticed pain in the upper molar area. Her medical history included an operation for PA in the hard palate that was performed 20 years previously. On imaging, four relatively well-defined lesions were demonstrated in the maxillary bone. She underwent an operation for these lesions. Each lesion revealed the same histological fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…In one case of MPA, Alkiba et al, compared immunohistochemical expression of PLAG1 with rearrangement of PLAG1 by RT-PCR in both the primary PA and MPA. They found that both the primary PA and MPA were positive for PLAG1 protein but neither tumor harbored the PLAG1 fusion gene [42].…”
Section: Discussionmentioning
confidence: 99%
“…In one case of MPA, Alkiba et al, compared immunohistochemical expression of PLAG1 with rearrangement of PLAG1 by RT-PCR in both the primary PA and MPA. They found that both the primary PA and MPA were positive for PLAG1 protein but neither tumor harbored the PLAG1 fusion gene [42].…”
Section: Discussionmentioning
confidence: 99%
“…40%-73% of recurrent tumours are multifocal as compared to 0.14%-0.6% in primary untreated pleomorphic adenoma [1] . Renehan et al have reported bone as the most common site for metastases (45%) followed by the head and neck (43%) and lung (36%) [4] .…”
Section: Discussionmentioning
confidence: 99%
“…However, when PSAs recur, they are associated with poorer outcomes and prognosis [1] . Pleomorphic adenoma in the thyroid gland has been described previously: one case in the right thyroid lobe [2] and the other as an incidental midline isthmic thyroid nodule [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Three types of malignancy have been reported to be associated with pleomorphic adenoma (PA): carcinoma ex‐pleomorphic adenoma (CXPA), carcinosarcoma, and metastasizing pleomorphic adenoma (MPA). The last of these is the least common, and to date only 50 MPA cases have been reported . The mechanism of the metastatic behaviour of MPA is still unknown, and it is speculated that the accumulation of key genetic alterations drives cancer progression, which is not always accompanied by histological changes …”
Section: Introductionmentioning
confidence: 99%